2018
DOI: 10.24820/ark.5550190.p010.387
|View full text |Cite
|
Sign up to set email alerts
|

An efficient protocol for the synthesis of N-fused 2, 5-diketopiperazine via base catalyzed Ugi-type MCR

Abstract: Numerous diversity-oriented synthesis of N-fused cyclic heterocycles have been demonstrated but most of them are based on point diversity within the same library and usually include slow sequential multistep synthesis, which also hurt from low yields and/or poor originator scopes. In current context, an efficient synthesis has been developed with the use of potassium carbonate as base under catalytically free reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…As observed (Table , entries 4, 12, 34, and 35), the use of bromine as the leaving group for the cyclization step did not result in the increase in the overall yield compared to the use of chlorine. With respect to the cyclization step alone (Scheme ), yields varied between 74 and 99%, values similar or even higher than those obtained for the cyclization stage via intramolecular N -alkylation in previous studies. ,, …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…As observed (Table , entries 4, 12, 34, and 35), the use of bromine as the leaving group for the cyclization step did not result in the increase in the overall yield compared to the use of chlorine. With respect to the cyclization step alone (Scheme ), yields varied between 74 and 99%, values similar or even higher than those obtained for the cyclization stage via intramolecular N -alkylation in previous studies. ,, …”
Section: Resultssupporting
confidence: 78%
“…With respect to the cyclization step alone (Scheme 3), yields varied between 74 and 99%, values similar or even higher than those obtained for the cyclization stage via intramolecular N-alkylation in previous studies. 10,15,16 Crystal Structures' Description. The discussion of structures will be divided into two groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. reported the cyclisation of Ugi peptidomimetic using a transition metal catalyst [ 35 ]. We modified the conditions for our reaction to eliminate the usage of a metal catalyst ( Table 2 , Scheme 3 , Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, recently Marccacini et al reported the ultrasound assisted synthesis in two steps of DKPs via Ugi-4CR followed by basic cyclization reaction under harsh basic conditions (Scheme 1a) [8]. In 2008 Naliapara et al reported an efficient synthesis of DKPs using mild basic and catalysis-free conditions at 100 C (Scheme 1b) [9]. Herein, we report a one-pot strategy for the synthesis of PHP like DKPs.…”
Section: Introductionmentioning
confidence: 94%